PENAMAAN AYAT AL QUR’AN SUATU DISKURSUS PENGEMBANGAN ILMU AL QUR’AN DAN TAFSIR (IAT) - Musyaffa Ahmad Rahim; Amirotun Nafisah (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2023)
This research aims to find the arguments used by a researcher in the field of the Al-Qur'an and Tafsir in naming one or a group of particular verses, besides that it aims to provide an overview of the open space for researchers in this field. Al-Qur'an and Tafsir use ijtihad in naming one or several verses. The study method follows the inductive method by tracing various references and sources of sharia sciences from the Al-Qur'an and the hadiths of the Prophet Muhammad SAW, as well as a search for classical commentary literature, and other references. This research concludes that the arguments and examples of giving